The Natural ways of vitamin D supplementation – detailed evaluation of Cantharellus cibarius - Naruszewicz, Maria; Midro, Aleksandra; Cetnarowski, Przemysław; Zagórski, Karol; Kozik, Mateusz; Skalksa-Dziobek, Nina; Małagocka, Weronika; Chybowska, Karolina; Rozpłoch-Sapa, Maria; Orłowski, Mateusz; et al. (Quality in Sport, 2024)
Introduction and purpose: In the past, fungi were considered a very low-value meal, however in modern literature, they are increasingly more frequently studied for their nutritional and medical properties. They are being currently reconsidered as an abundant source of nutrients that may be incorporated in diets of individuals of special medical needs, such as obese and diabetic patients. The purpose of this review is to evaluate one of the most common edible mushroom species, Cantharellus cibarius (girolle, golden chanterelle) for its health promoting properties with particular emphasis on its vitamin D content. It was of considerable importance for us to analyse the amount of vitamin D in the mentioned mushroom, as this micronutrient deficiency is fairly common in the human population. Material and method: The available literature was reviewed as provided by PubMed database and Google Scholar, with the use of keywords. State of knowledge: Golden chanterelle mushroom is a valuable source of proteins, mineral ingredients like potassium, phosphorus, magnesium, iron and calcium, while containing low amounts of sodium and fat. The mushroom is especially valuable for its rich content of vitamin D, ranging up to 63 μg/100g fresh weight. Conclusions: This paper may help other scientists expand their research on golden chanterelle properties. Moreover, girolle, as naturally containing many pro-health metabolites, may serve as natural supplementation of microelements.